How to predict a difficult airway: Kako napovedati težavno oskrbo dihalne poti - Mekiš, Dušan (Acta Medico-Biotechnica, 2021)
According to The American Society of Anaesthesiologists Task Force, a difficult airway is defined as a clinical situation in which a conventionally– trained anaesthesiologist experiences difficulty with face mask ventilation and/or difficulty with tracheal intubation. Failing at efficient airway management is a source of major apprehension for physicians. Predicting difficult airway management is a mandatory part of clinical practice for paediatric and adult patients so as to avoid unexpected difficult airway management and adverse outcomes. Predicting a difficult airway is based on a focused medical history, review of prior medical records, physical examination, and specific tests for airway assessment. Each feature or airway test has its own sensitivity and specificity for the prediction of a difficult airway. All airway assessment tests are characterised by low sensitivity, reasonable specificity, and a low positive predictive value. Several scoring system models have been developed by multivariate analysis with multiple different integrated tests or risk factors to improve the prediction of a difficult airway, but with considerably different effectiveness to predict a difficult airway. According to the European Society of Anaesthesiology, systematic multimodal screening before airway management should include the Mallampati classification and thyromental distance, mouth opening or interincisor distance, range of motion of head and neck, compliance of the mandibular space, and the upper lip bite test.